PELAKSANAAN PENYIDIKAN TERHADAP TINDAK PIDANA YANG DILAKUKAN OLEH ANAK DIBAWAH UMUR DI POLISI RESORT KOTA PEKANBARU - Hasanah, Roudhotul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Lately a lot of crimes committed by children under the age of ever morealarming, in Pekanbaru City Police Resort, in February 2012 there were abunch of kids throwing junior high school students to take action against thePolice Headquarters Resort City (Mapolresta ) Pekanbaru, and theperpetrators of the attacks consisted of 17 (Seventeen) children, and 15(Fifteen) The child is still under age. Implementation investigations of juveniledelinquents, including the investigator shall examine the suspect in a familyatmosphere and the interrogation of juvenile delinquents must be keptconfidential. The purpose of this thesis, namely: First, the implementation ofthe investigation of the offenses committed by minors in Pekanbaru CityPolice Resort, Second, Limitations to the investigation of criminal offensescommitted by minors in Pekanbaru City Police Resort, Third, efforts done toovercome barriers to the implementation of the investigation of criminaloffenses committed by minors in Pekanbaru City Police Resort.This type of research can be classified into types of juridical sociologicalresearch, which means reviewing the state of the existing problems in the fieldassociate with aspects of the applicable law and governing problems. Becausein this study the authors directly conduct research on the location or placeunder study in order to provide a complete and clear picture of the problemunder study, the research was conducted in Pekanbaru City Police Resort,while the population and the sample is to be a set of objects based onmeticulous research sites. The data used are primary data, secondary data anddata tertiary, technical data collection using interviews and literature study.From the results of research and discussion, it is concluded that the First,implementation of the investigation of the offenses committed by minors inPekanbaru City Police Resort does not run properly because it is not inaccordance with Law No. 3 of 1997 on Juvenile Justice, Second, obstacles toimplementation investigations of criminal offenses committed by minors inPekanbaru City Police Resort is difficulty finding evidence, the study durationof Correctional Agency (BAPAS), absence of special detention for children,Third, efforts were made to overcome barriers to the implementation of thecriminal investigation committed by minors in Pekanbaru City Police Resort isBringing a suspect to a crime scene to find evidence, provide information to he Bureau of Corrections (BAPAS) to accelerate the research completed,submit the budget for the construction of detention for children and women.Keywords: Implementation-Investigation-Crime-Children under Age